Angolan civil society activism since the 1990s: reformists, confrontationists and young revolutionaries of the ‘Arab spring generation’ - Vidal, N. (Review of African Political Economy, 2015)
Aiming for regime transformation, post-transition Angolan civil society activism moved from reformism and confrontationism to ultra-confrontationism. Reformism and confrontationism evolved until the 2008 elections, influenced by development thinking (neoliberalism/institutionalism vs neo-Marxism/world-system thinking), in two opposing strategies: ‘constructive engagement’ vs political defiance. The dispute ended with ultra-confrontationism gaining impetus with the Arab spring, with a younger generation resorting to new methods (information and communications technology and demonstrations). Despite the lack of funding or international links, the newer methods caused more concern to the regime. Nevertheless, they suffer from the same shortfalls as their predecessors: they are confined to an urban/suburban social segment, and unable to attract the majority of the population.